Response of fiscal efforts to oil price dynamics. (March 2023) - Abubakar, Attahir Babaji; Muhammad, Mansur; Mensah, Samuel
Abstract: This study investigates the response of Nigeria's government balance to oil price dynamics. The Linear and Non-Linear Autoregressive Distributed Lag models are employed for analysis. The findings of the study reveal that while the long run response of government balance to oil price dynamics is symmetric, the short run response is asymmetric. In the long run, an increase in oil price improves the government's fiscal position, signifying an increase in fiscal effort. Interestingly, while positive oil price shocks lead to a short run worsening of the government's fiscal position, indicating poor fiscal efforts, negative oil price shocks influence an improvement of government fiscal efforts. Further, although the operationalisation of fiscal rules worsens the government's fiscal position in the short run, it has a beneficial long run effect. These findings have far-reaching policy implications. Highlights: The study investigates the response of government fiscal efforts to oil price dynamics. The Linear and Non-Linear ARDL models are applied for analysis. The response of fiscal effort to oil price dynamics is symmetric (asymmetric) in the long run (short run). The goal of maintaining strong fiscal health dominates in the long run. Fiscal expansion goals dominate in the short run.